Mutant Ferritin L-chains That Cause Neurodegeneration Act in a Dominant-negative Manner to Reduce Ferritin Iron Incorporation - Luscieti, Sara (American Society for Biochemistry and Molecular Biology, 2010)
Nucleotide insertions that modify the C terminus of ferritin light chain (FTL) cause neurodegenerative movement disorders named neuroferritinopathies, which are inherited with dominant transmission. The disorders are characterized by abnormal brain iron accumulation. Here we describe the biochemical and crystallographic characterization of pathogenic FTL mutant p.Phe167SerfsX26 showing that it is a functional ferritin with an altered conformation of the C terminus. Moreover we analyze functional and stability properties of ferritin heteropolymers made of 20–23 H-chains and 1–4 L-chains with representative pathogenic mutations or the last 10–28 residues truncated. All the heteropolymers containing the pathogenic or truncated mutants had a strongly reduced capacity to incorporate iron, both when expressed in Escherichia coli, and in vitro when iron was supplied as Fe(III) in the presence of ascorbate. The mutations also reduced the physical stability of the heteropolymers. The data indicate that even a few mutated L-chains are sufficient to alter the permeability of 1–2 of the 6 hydrophobic channels and modify ferritin capacity to incorporate iron. The dominant-negative action of the mutations explains the dominant transmission of the disorder. The data support the hypothesis that hereditary ferritinopathies are due to alterations of ferritin functionality and provide new input on the mechanism of the function of isoferritins.